Can a 3D woven GFRP composite really provide better impact resistance compared to a 2D woven GFRP composite at all of the thicknesses?. (January 2022) - Kazemianfar, Behzad; Nami, Mohammad Rahim
Abstract: The large majority of previous studies about comparison of impact response of 2D and 3D woven composites focused on thin laminates but not thicker ones. Thus, the aim of this study is to determine whether thicker 3D laminates exhibit better impact resistance compared to 2D ones or not. For this purpose, firstly several tensile tests were performed on the composite specimens in nine different thicknesses. In fact, the longitudinal tensile modulus extracted from tensile tests was used to determine delamination threshold load of them. Then, 2D and 3D laminates with an identical thickness were tested by drop weight tower under several energies to specify the perforation and penetration energy thresholds. Finally, 2D and 3D composites with nine different thicknesses were subjected to impact loading to investigate their impact behavior. The experimental results revealed that the relationship between thickness and delamination threshold load of 2D woven E-glass/unsaturated polyester composites can be fitted with a power regression function. The extracted empirical function was also validated with the analytical results obtained from a simple method based on mode II fracture toughness of laminates. Contrary to what is normally believed, the value of energy absorption in 2D specimens has no dependency on their thickness. In addition, analysis of results in terms of energy absorption, damage area and damage initiation load indicated that thicker 2D woven fabrics exhibit higher impact resistance compared to 3D ones unlike thinner laminates.